Burkina Faso : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
The Joint Staff Advisory Note (JSAN) of the Poverty Reduction Strategy Paper on Burkina Faso reviews poverty trends, characteristics, and strategies for its reduction. The macroeconomic framework is based on an average real growth rate of about 6 1\2 percent, which is in line with the average growth rate. The potential for enhancing tax revenues notwithstanding, additional donor support would be needed, and should be provided principally in the form of grants, given Burkina Faso's high level of external debt.